The Women and the Law: From Protection to Criminalization - Prasetyawati, Endang; firmansyah, M; Permana, M Riski; Ramadhan, Yananda Putra (The Future of Education Journal, 2025)
The position of women within Indonesia's legal system is often complex and vulnerable. Although legal norms formally guarantee protection for women, in practice, many cases reveal that women instead become re-victimized by the legal process itself. This paper aims to examine the shift in women’s status from victims to offenders in various criminal cases. The study employs a normative juridical approach combined with case study analysis. By reviewing cases involving domestic violence, human trafficking, and drug-related offenses, the research finds that structural factors such as gender inequality, power imbalances, and biases within law enforcement contribute to the criminalization of female victims. These findings highlight the urgent need for legal reform that incorporates a gender justice perspective as an integral part of Indonesia’s broader legal reform agenda.